Fabrication and physical properties of pipe based on fiberglass reinforced with plastic waste in-plant application system - Marsi, Noraini; Mohd Fodzi, Muhammad Haikal; Subramaniam, Lingeshvaran; Mohd Rus, Anika Zafiah; Esa, Faizal; Wan Abdul Rahman, Wan Mohd Wardi (Penerbit UTHM, 2020)
The word "waste" comes a vision of a material with no worth or helpful purpose. However, technology is evolving that holds promise for mistreatment waste or recycled plastics to create an array of high-performance composite product that are themselves doubtless reusable. The plastic waste is currently a significant environmental threat to current civilisation...